The Effect of Nutrition Course on The Level of Nutrition Knowledge - Yilmaz, Gürkan; Şeker, Ramazan (Progress in Nutrition, 2020)
Study Objectives: It is a well-known fact that knowledge about athletes 'and coaches' nutrition is very important. There are several studies on the nutrition of athletes. In this study, in order to determine the athletes’ nutritional knowledge levels; it was conducted to determine the sports knowledge scores of the students, the future coaches of today's athletes, study in the Faculty of Sports Sciences. Methods: 394 students voluntarily participated in the study. "Sports Nutrition Knowledge Scale (SNKS)" was used to determine students' sports nutrition knowledge scores. Independent T test was used to compare the groups, and OneWay ANOVA test was used to determine the difference between the departments. Results: As a result of the analysis, the average knowledge score of the students who took the nutrition course was determined as 37.11% and the average knowledge score of the students who did not take the nutritional course was determined as 22.67%. It was determined that the difference between the nutritional knowledge average score of the students who took and did not take a nutritional course was in favor of the students taking a nutritional course. While the nutritional knowledge average scores of male students were 30.23, the average of nutritional knowledge of female was 29.50. No difference was found in the comparison of the nutritional knowledge score averages of male and female students. The average of nutritional knowledge scores among the departments in the Teaching Department was found to be 32.52 in the Coaching department and 27.01 in the Management Department. When the sub-dimensions were evaluated, there was a significant difference in factor3microbeosinologies, factor4sporting, factor5suplement, factor6alcohol dimensions. Conclusion: As a result, it was determined that the nutritional knowledge levels of the students who took both nutrition courses and those who did not take the nutritional courses were found to be poor, while the nutritional knowledge total scores of the students who took the nutritional courses were higher. For this reason, it is thought that it will be beneficial to increase the nutrition course duration and to add these courses to the standard education as a compulsory course in order to keep the nutritional knowledge levels of the students who can coach in the future.